Longissimus dorsi fatty acids composition of Bos indicus and Bos indicus x Bos taurus crossbred steers finished in pasture - Prado,Ivanor Nunes do (2003)
Studies were carried out to evaluate the fatty acids composition of Longissimus dorsi muscle, with or without fat thickness, of Bos indicus and Bos indicus x Bos taurus crossbred steers finished in millet (Pennisetum americanum L.) or star grass (Cynodon plectostachyus Pilger) pasture systems with mineral or mineral protein supplementation. Neither the treatment nor the genetic group had effect on meat fatty acids composition. The cut had effect on meat fatty acid composition. The meat without fat thickness had 11% of PUFA, 43% of MUFA and 45% of SFA. The meat with fat thickness had 5% of PUFA, 44% of MUFA and 50% of SFA. PUFA/SFA ratio was 0.10 and 0.25 and n-6/n-3 ratio was 0.80 and 1.27 for cuts with and without fat thickness.